Effect of the Presence of Basements on the Vibration Period and Other Seismic Responses of R.C. Frames - Alomari, J. A. (Engineering, Technology & Applied Science Research, 2019)
The soil-structure interaction (SSI) of R. C. building frames including basements below ground level has been the subject of extended research, mostly in the form of theoretical dynamic analysis. There are different issues concerned with this type of work, as e.g. the location of the base of the structure. Usually, the base of the structure in dynamic analysis or according to the codes is the level at which the lateral displacement is zero. According to this definition, and with the presence of basement floors and the soil mass below, the ground level may not be the base of the structure. The soil stiffness around basement walls has a great effect on the lateral displacement of the basement floor. Another issue is the effect of the presence of the basement floors on the dynamic behavior of the structure. A third issue is the effect of the soil around the basement walls and the soil mass below the foundation in general, which is known as the SSI. In this paper, 3-dimensional regular building frames subjected to seismic loading are analyzed using SAP2000 software. The first frame is a 5-floor, 3-D frame without including the soil mass below the raft foundation and without a basement floor. The second frame is the same frame with a basement floor and with consideration of the soil mass below the raft foundation and around the walls of the basement floor. The third frame is the same frame with consideration of the soil mass below the raft foundation but without the basement floor. Results of the seismic time history analysis and UBC97 response spectrum analysis are presented and discussed.